Pengaruh Varietas dan Jarak Tanam terhadap Efisiensi Radiasi, Pertumbuhan dan Hasil Jagung Manis (Zea mays saccharata Sturt.) Di Lahan Rawa Lebak - Majedi; Gusti Rusmayadi; Wahdah, Raihani (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2022)
In Indonesia, corn is a plant that has a function as a source of food, a source of feed and the main ingredient for industry. However, it has not been able to meet market demand for corn because it is constrained by several factors such as lowland swamp land which is used as a place of cultivation with all the problems, namely periodically inundated land, low soil fertility, high soil acidity, toxic substances, lack of micro nutrients, organic matter still raw and others. The objectives of the study were: 1) Analyzing the interaction of varieties with spacing on radiation efficiency, growth and yield of sweet corn (Zea mays saccharata Sturt.) in lowland swamp land. 2) Analyzing the best varieties and the best spacing for radiation efficiency, growth and yield of sweet corn (Zea mays saccharata Sturt.) in lowland swamp land. This research was conducted in Muara Tapus Village, North Hulu Sungai Regency, South Kalimantan Province in May - August 2021 using the Factorial Randomized Design method. The first factor is the sweet corn variety (V) consisting of four levels, namely exotic variety (v1), jamboree variety (v2), talent variety (v3) and ganebo variety (v4). The second factor is sweet corn planting distance (J) consisting of three levels, namely 75 cm x 20 cm (j1), 75 cm x 25 cm (j2) and 75 cm x 30 cm (j3). The results showed that the interaction between varieties and spacing did not affect all observation variables. Varieties affect the observed variables of plant height, number of leaves, leaf area index, plant growth rate and number of rows per ear. Spacing affects the observed variables of plant height, leaf area index and plant growth rate. The best variety is the talent variety (v3) and the best spacing is 75 cm x 20 cm (j1) and the radiation utilization efficiency value is 1.5584 g.MJ-1.